Measurement of the effective weak mixing angle by jet-charge asymmetry in hadronic decays of the Z boson - Dova, María Teresa (1998)
The coupling of the Z boson to quarks is studied in a sample of about 3.5 million hadronic Z decays collected by the L3 experiment at LEP from 1991 to 1995. The forward–backward quark charge asymmetry is measured by means of a jet charge technique. From the measured asymmetries, the effective weak mixing angle is determined to be <mtext>sin</mtext>2<mtext>θ</mtext><mtext>W</mtext><mtext>=0.2327±0.0012(stat.)±0.0013(syst.)</mtext>.